The Influence of Customer Trust and Customer Satisfaction on Customer Loyalty at PT. Bima Finance Lahat - Intan Putri Pratama; Kasinem Kasinem; M. Pahlan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the effect of customer trust on customer loyalty at PT. Bima Finance Lahat. To determine the effect of customer satisfaction on customer loyalty at PT. Bima Finance Lahat. To determine the joint effect of customer trust and customer satisfaction on customer loyalty at PT. Bima Finance Lahat. This study is quantitative, using statistical calculations using multiple linear regression, partial tests (t-test), simultaneous tests (f-test), and coefficients of determination. The analysis results show that customer trust has a significant effect on customer loyalty at PT. Bima Finance Lahat. Customer satisfaction has a significant effect on customer loyalty at PT. Bima Finance Lahat. Customer trust and customer satisfaction have a significant joint effect on customer loyalty at PT. Bima Finance Lahat.